Obstructive sleep apnoea as a risk factor for osteopenia and osteoporosis in the male population: further data and comments. Issue 4 (13th April 2017) - Liguori, Claudio; Piccirilli, Eleonora; Izzi, Francesca; Mercuri, Nicola Biagio; Tarantino, Umberto; Placidi, Fabio
We have recently read some criticisms raised from Sforza et al . [1] in Sleep Medicine about our paper entitled "Obstructive sleep apnoea as a risk factor for osteopenia and osteoporosis in the male population" published in the European Respiratory Journal last March [2]. In the latter, we reported the significant reduction of the bone mineral density in a large population of male severe obstructive sleep apnoea (OSA) patients (apnoea–hypopnoea index >30 events per h) compared to a population of age- and body mass index (BMI)-matched controls [2]. Since we published our report as a research letter we could not provide the full data, neither in the manuscript nor in the form of supplementary material [2]. For this reason we write this correspondence in order to specify our results and to respond to the criticisms from Sforza et al . [1], and thank the Editor for giving us this opportunity. We would specify that in the previous study of our group we included consecutive male OSA patients admitted to our outpatient clinic, who underwent polygraphic cardiorespiratory monitoring according to the American Academy of Sleep Medicine criteria [3]. Since the aim of our study was to evaluate the possible influence of severe OSA on bone mineral density in the male population, we ruled out possible confounding factors that might have reduced the reliability of our results by excluding all the patients who presented one or more conditions with known influence on bone health (see exclusion criteria of the previous paper) [2]. Therefore, we excluded 148 out of 240 male OSA patients since: 67 were affected by diabetes, 31 had chronic obstructive pulmonary disease, four showed thyroid dysfunction, three reported use of corticosteroids in the 4 weeks preceding the inclusion in the study, 29 reported diuretic treatments, nine reported vitamin supplements consumption and five had history of fractures. Moreover, we compared the group of 92 male OSA patients to a group of 50 male subjects who were age- and BMI-matched with OSA patients not showing OSA syndrome (OSAS) at the polygraphic recording. OSAS has been defined according to the recent International Classification of Sleep Disorder, 3rd edition (ICSD3) (table 1 ) [4]. Obstructive sleep apnoea as a risk factor for osteopenia and osteoporosis in males: further data and comments http://ow.ly/RNCJ309KtPp